The impact of work spirit on the performance of employees and its reflection in the evaluation of their organizational units - a case study at the Technical Institute in Mosul - عبد الستار محمد علي,; ميسون عبدالله الشلمة, (Iraqi Journal for Administrative Sciences, 2025)
This research aims to profile the subject may be new to thinking regulatory not a subject that spiritual work, and in the context of a case study included to test the impact of these spiritual performance of staff and reflected in the assessment of their units regulators, which numbered nine sections, which were randomly selected from among the units or departments of the Institute of Scientific and Technical Mosul\'s Overall (22) section scientifically. After he finished two researchers from the development of a methodology their research including the identification of society represented Baltdrisien working in academic departments examined, and was appointed whose strength (98) pedagogy and the associated preparation of form-resolution five-year standard, legally framework theory for consideration, which included an appropriate definition in the spirit of the work and its importance and dimensions (content Values of the organization\'s goals, relationships and justice, organizational), as well as the subject of performance, effectiveness and mechanisms of evaluation, and then moved later to the frame field,under which the statistical analysis and access to test hypotheses by adopting the correlation coefficient and linear regression for a variety of data obtained from sample of their research to benefit from Form-resolution mentioned, as well as the rest of the data obtained it by interviews with relevant performance campus of the Institute mentioned, and others who are involved in assessing this performance, has been reached based on the analysis referred to a number of results that helped them out many of the conclusions, the most important of which is proven link availability and the impact of legal entities with the spirit of the work performance of employees, as well as an important reflection of the availability of such impact as result of scientific evaluation of their units. In light of these findings forward a number of proposals, the most important of which urged the administration urged the Institute to further the performance of its Institute of attention all the way to turn it into the form that marked by the spiritual nature of performance in light of the characteristics of this performance as reflected in the theoretical framework for research.